Study of Physical and Chemical Properties of Solid Dispersions of Quercetin - Inna, Dr. Kovalevska (Asian Journal of Pharmaceutics (AJP), 2018)
Aim: Increasing solubility of medicinal substances is a major problem in the pharmacy, since about 40% of produced pharmaceutical substances are poorly soluble, and of newly synthesized substances up to 60% have low solubility in water and aqueous solutions. For poorly soluble drugs, the limiting stage of the absorption process is usually the rate of its dissolution, and therefore, much attention is paid to the development of ways to increase it. To solve this problem, a number of methods are used which can be conditionally divided into physical and chemical. Materials and Methods: Objects of the study were chosen quercetin, quercetin solid dispersions (SDs) with polyvinylpyrrolidone (PVP), polyethylene oxide (PEO)-6000, and β-cyclodextrin (β-CD). The solubility of the samples was studied spectrophotometrically. The particles’shape and size were studied using microscopic analysis. X-ray diffraction analysis was performed on a DRON-3 installation at monochromatic radiation Ka - Cu (λ = 1.54 Ǻ) by recording diffraction mappings on the diffractogram tape in the angular range 2θ = 5–500. Results and Discussions: In the article, the results of solubility study of quercetin and its SDs based on PVP, PEO, and β-CD obtained by melting with the removal of solvent are presented. The results obtained suggest the possibility of quercetin polymorphic transformations in the composition of SD. Polymer effect on increasing the solubility of quercetin in the composition of the SD has been shown. Conclusion: Using physicochemical methods of analysis, change in the crystal structure of quercetin under the influence of high-molecular substances has been proved.